Pengembangan Literasi Bahasa Anak Usia Dini - Resti Yulia; Delfi Eliza (Pusat Penerbitan Universitas (P2U) Unisba, 2021)
This study aims to describe the development of language literacy in early childhood, which is one of the skills needed in the 21st century. Early childhood is the focus of instilling 21st century skills because at this age it is the foundation age for the development of all aspects of child development. The development of aspects of child development will help children to have life skills and skills so that they can interact well in their environment. One aspect of child development that will help children in their interactions is language development. The method used in this research is literature review with sources of journals, articles and books. The literature review method was chosen with the aim of obtaining an in-depth theoretical picture of early childhood language literacy. Language literacy is one of the skills that must be possessed by early childhood. The results of the study found that the definition of language literacy is conventionally interpreted as literacy which has an effect on rigid development such as learning to read and write while sitting neatly and writing on the table. Nowadays, the definition of language literacy development has developed into literacy skills that are adapted to children's language development. Therefore, at the level of language literacy development in AUD, the expertise of teachers is needed in packaging learning and the school environment as a source and media for student learning.Keywords: Literacy; Development of Language Literacy; Early Childhood. AbstrakPenelitian ini bertujuan mendeskripsikan pengembangan literasi berbahasa pada anak usia dini, yang merupakan salah satu keterampilan yang dibutuhkan pada Abad 21. Usia dini menjadi fokus menanamkan kecakapan abad 21 karena pada usia ini merupakan usia pondasi pengembangan semua aspek perkembangan anak. Pengembangan aspek perkembangan anak akan membantu anak memiliki keterampilan dan kecakapan hidup agar dapat berinteraksi dengan baik di lingkungannya. Salah satu aspek perkembangan anak yang akan membantu anak dalam interaksinya adalah perkembangan bahasa. Metode yang digunakan dalam penelitian ini adalah kajian literature dengan sumber jurnal, artikel dan buku. Metode kajian literatur dipilih dengan tujuan mendapatkan gambaran teoritis secara mendalam tentang litarasi berbahasa anak usia dini. Literasi berbahasa merupakan salah satu keterampilan yang harus dimiliki oleh anak usia dini. Hasil kajian menemukan bahwa definisi literasi bahasa secara konvensional ditafsirkan sebagai kemampuan baca tulis berefek pada pengembangan yang kaku seperti belajar membaca dan menulis dengan duduk rapi dan menulis diatas meja. Pada zaman sekarang definisi pengembangan literasi bahasa mengalami perkembangan menjadi kemampuan baca tulis yang disesuaikan dengan perkembangan bahasa anak. Oleh sebab itu, dalam tataran pengembangan literasi bahasa pada AUD diperlukan kepiawaian guru dalam mengemas pembelajaran dan lingkungan sekolah sebagai sumber dan media belajar siswa.Kata Kunci: Literasi; Pengembangan Literasi Berbahasa; Anak Usia Dini.